ANALISIS CLUSTERING ZONASI RAWAN BENCANA PADA KANTOR BASARNAS PROV. JAMBI MENGGUNAKAN METODE K-MEANS: Clustering;K-Means;Basarnas. - Limia Budiarti, Rike; Rahayu, Muh. Subur (JURNAL AKADEMIKA, 2022)
Indonesia is one of the countries that passes through the Pacific Ring of Fire or commonly called the Pacific Ring of Fire. The area is an area that often occurs natural disasters such as floods, droughts and hurricanes. The National SAR Agency (Basarnas), which is an Indonesian Non-Ministerial Government Institution that carries out tasks in the field of search and rescue (Search And Rescue / SAR). Natural disasters can occur suddenly or through a process that takes place slowly. In some types of disasters such as hurricanes, it is almost impossible to accurately predict when, where, and where they will occur. The shock occurred due to a lack of vigilance and preparedness in dealing with the threat of danger, resulting in many fatalities, injuries and material losses. For this reason, efforts are urgently needed to bring about the impact of disasters. In this study, the method used in grouping the data is K-Means clustering. The result of this research is the grouping of disaster-prone and non-disaster-prone areas which are represented in the Geographical Information System (GIS). Based on the grouping using K-Means Prov. Jambi is divided into 2 disaster groups with the characteristics of disaster-prone areas and non-disaster-prone areas. The 2 groups have validated their accuracy. Cluster 1 includes the city of Jambi, which has high rainfall and causes flooding, while cluster 2 includes Kerinci, Sarolagun, Batanghari, Muaro Jambi, East Tanjung Jabung, West Tanjung Jabung, Tebo, Bungo, Sungai Penuh City.